Implementation of Sharia Accounting in the Financial Statements of Zakat Institutions: A Case Study at BAZNAS - Nasoha, Ahmad Muhamad Mustain; Atqiya, Ashfiya Nur (ASFA Foundation, 2025)
Zakat is a fundamental pillar of the Islamic economic system, playing a vital role in reducing poverty and ensuring a fair distribution of wealth within society. This study seeks to explore how zakat accounting is practiced by zakat institutions in Indonesia, with particular attention to transparency, accountability, and adherence to Sharia-compliant accounting standards. Using a qualitative research approach, data were gathered through in-depth interviews with zakat institution managers, a review of financial reporting documents, and direct observations of zakat management processes. The findings reveal that while many institutions have made efforts to adopt appropriate accounting standards, significant challenges remain—particularly in maintaining transparency and accountability—which in turn influence public trust. This study highlights the need for improved financial reporting systems and the integration of information technology to enhance oversight and encourage greater community involvement in zakat administration. It is hoped that these insights will contribute to the advancement of zakat accounting practices and promote better governance across zakat institutions in Indonesia.